Every Breath You Take: The Impact of Environment on Resident Memory CD8 T Cells in the Lung - Shane, Hillary L.; Klonowski, Kimberly D. (Frontiers in Immunology, 2014)
Resident memory T cells (TRM) are broadly defined as a population of T cells which persist in non-lymphoid sites long term, do not re-enter the circulation, and are distinct from central memory T cells (TCM) and circulating effector memory T cells (TEM). Recent studies have described populations of TRM cells in the skin, gut, lungs and nervous tissue. However, it is becoming increasingly clear that the specific environment in which the TRM reside can further refine their phenotypical and functional properties. Here, we focus on the TRM cells that develop following respiratory infection and reside in the lungs and the lung airways. Specifically, we will review recent studies that have described some of the requirements for establishment of TRM cells in these tissues, and the defining characteristics of TRM in the lungs and lung airways. With continual bombardment of the respiratory tract by both pathogenic and environmental antigens, dynamic fluctuations in the local milieu including homeostatic resources and niche restrictions can impact TRM longevity. Beyond a comprehensive characterization of lung TRM cells, special attention will be placed on studies which have defined how the microenvironment of the lung influences memory T cell survival at this site. As memory T cell populations in the lung airways are requisite for protection yet wane numerically over time, developing a comprehensive picture of factors which may influence TRM development and persistence at these sites is important for improving T cell-based vaccine design.